Characterization of a New Trioxilin and a Sulfoquinovosyl Diacylglycerol with Anti-Inflammatory Properties from the Dinoflagellate Oxyrrhis marina - Eun Young Yoon; A. Reum Yang; Jaeyeon Park; Seung Joo Moon; Eun Ju Jeong; Jung-Rae Rho (Marine Drugs, 2017)
Two new compounds—a trioxilin and a sulfoquinovosyl diacylglycerol (SQDG)—were isolated from the methanolic extract of the heterotrophic dinoflagellate Oxyrrhis marina cultivated by feeding on dried yeasts. The trioxilin was identified as (4Z,8E,13Z,16Z,19Z) -7(S),10(S),11(S)-trihydroxydocosapentaenoic acid (1), and the SQDG was identified as (2S)-1-O-hexadecanosy-2-O-docosahexaenoyl-3-O-(6-sulfo-α-d-quinovopyranosyl)-glycerol (2) by a combination of nuclear magnetic resonance (NMR) spectra, mass analyses, and chemical reactions. The two compounds were associated with docosahexaenoic acid, which is a major component of O. marina. The two isolated compounds showed significant nitric oxide inhibitory activity on lipopolysaccharide-induced RAW264.7 cells. Compound 2 showed no cytotoxicity against hepatocarcinoma (HepG2), neuroblastoma (Neuro-2a), and colon cancer (HCT-116) cells, while weak cytotoxicity was observed for compound 1 against Neuro-2a cells.